Use of GeneXpert for the diagnosis of multidrug resistant pulmonary tuberculosis among smear negative suspected tuberculosis cases in Nepal - Subedi, Shishir; Pant, Narayan Dutt; Adhikari, Nabaraj; Shrestha, Upendra Thapa; Shrestha, Bhawana (Janaki Medical College Journal of Medical Science, 2017)
Not Available. Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 50-52